Selection of coastal estuarine habitats by atherina boyeri larvae in laboratory experiments - Gonçalves, Renata Isabel de Sousa (2014)
Coastal wetlands are important nursery areas for many fish species as they provide food, refuge from predators and optimal hydrodynamic conditions. The impact of anthropogenic and environmental changes on ecological functions of these areas need to be identified as a basis for establishing adequate ecohydrological measures for the long-term sustainability of the ecosystem and its associated services. Patterns of habitat selection were examined in wild-caught larvae of Atherina boyeri (Risso, 1810), by means of microcosms experiments. We simulated three habitats representative of vertical marsh profile at Guadiana wetland, non-vegetated bottom (sand) and two vegetation types (Spartina maritima and Sarcorcornia spp.), in experimental units and monitored fish larvae spatial distribution by video-recording. We observed a strong avoidance of both vegetated habitats suggesting that habitat choice behavior may be dependent on external stimuli such as current velocity, predator effect and food availability. Similar experiments including external factors are required to unravel the behavioral responses of A. boyeri to different types of habitat.